2020
DOI: 10.1186/s12866-020-01981-7
|View full text |Cite|
|
Sign up to set email alerts
|

A network approach to investigating the key microbes and stability of gut microbial communities in a mouse neuropathic pain model

Abstract: Background Neuropathic pain is an abnormally increased sensitivity to pain, especially from mechanical or thermal stimuli. To date, the current pharmacological treatments for neuropathic pain are still unsatisfactory. The gut microbiota reportedly plays important roles in inducing neuropathic pain, so probiotics have also been used to treat it. However, the underlying questions around the interactions in and stability of the gut microbiota in a spared nerve injury-induced neuropathic pain model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 83 publications
0
19
0
Order By: Relevance
“…Of the 48 full texts reviewed, only 15 articles met the set inclusion criteria (Figure 1). The reviewed articles encompassed 13 studies using various animal models (Sommer et al, 2001;Gwak et al, 2006; ("neuropath"):ti,ab,kw AND ("microbiota"):ti,ab,kw ("neuropathic pain"):ti,ab,kw AND ("bacteria"):ti,ab,kw ("nerve pain"):ti,ab,kw AND ("gut microbe"):ti,ab,kw ("neuralgi"):ti,ab,kw AND ("gut bacteria"):ti,ab,kw ("neuropathy"):ti,ab,kw AND ("gut microbiome"):ti,ab,kw ("neuropath"):ti,ab,kw AND ("probiotics"):ti,ab,kw ("neuropathy"):ti,ab,kw AND ("prebiotics"):ti,ab,kw ("neuropathic"):ti,ab,kw AND ("synbiotic"):ti,ab,kw ("neuropathic pain"):ti,ab,kw AND ("postbiotic"):ti,ab,kw ("neuralgia"):ti,ab,kw AND ("chemotherapy"):ti,ab,kw ("neuropathy"):ti,ab,kw AND ("chemo-induced"):ti,ab,kw ("neuropathic pain"):ti,ab,kw AND ("chronic constriction injury"):ti,ab,kw ("neuropathy"):ti,ab,kw AND ("nerve-CCI"):ti,ab,kw ("neuropathic pain"):ti,ab,kw AND ("chronic constriction nerve injury"):ti,ab,kw ("neuralgia"):ti,ab,kw AND ("spinal injury"):ti,ab,kw ("hyperalgesia"):ti,ab,kw AND ("spinal nerve injury"):ti,ab,kw ("neuropathic pain"):ti,ab,kw AND ("SNI"):ti,ab,kw: ("hyperlagesia"):ti,ab,kw AND ("spared nerve injury"):ti,ab,kw: (((1 OR 3) AND 3 AND 5) OR ( 5 Austin et al, 2012;Bráz et al, 2012;Wardill et al, 2016;Shen et al, 2017;Ramakrishna et al, 2019;Yang et al, 2019;Brandon-Mong et al, 2020;Chen et al, 2021;Cuozzo et al, 2021;Ding et al, 2021;Lian et al, 2021), a single in vitro study (Castelli et al, 2018), and a single randomised controlled trial (RCT) with 327 enrolled participants, Table 2 (Ellis et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 48 full texts reviewed, only 15 articles met the set inclusion criteria (Figure 1). The reviewed articles encompassed 13 studies using various animal models (Sommer et al, 2001;Gwak et al, 2006; ("neuropath"):ti,ab,kw AND ("microbiota"):ti,ab,kw ("neuropathic pain"):ti,ab,kw AND ("bacteria"):ti,ab,kw ("nerve pain"):ti,ab,kw AND ("gut microbe"):ti,ab,kw ("neuralgi"):ti,ab,kw AND ("gut bacteria"):ti,ab,kw ("neuropathy"):ti,ab,kw AND ("gut microbiome"):ti,ab,kw ("neuropath"):ti,ab,kw AND ("probiotics"):ti,ab,kw ("neuropathy"):ti,ab,kw AND ("prebiotics"):ti,ab,kw ("neuropathic"):ti,ab,kw AND ("synbiotic"):ti,ab,kw ("neuropathic pain"):ti,ab,kw AND ("postbiotic"):ti,ab,kw ("neuralgia"):ti,ab,kw AND ("chemotherapy"):ti,ab,kw ("neuropathy"):ti,ab,kw AND ("chemo-induced"):ti,ab,kw ("neuropathic pain"):ti,ab,kw AND ("chronic constriction injury"):ti,ab,kw ("neuropathy"):ti,ab,kw AND ("nerve-CCI"):ti,ab,kw ("neuropathic pain"):ti,ab,kw AND ("chronic constriction nerve injury"):ti,ab,kw ("neuralgia"):ti,ab,kw AND ("spinal injury"):ti,ab,kw ("hyperalgesia"):ti,ab,kw AND ("spinal nerve injury"):ti,ab,kw ("neuropathic pain"):ti,ab,kw AND ("SNI"):ti,ab,kw: ("hyperlagesia"):ti,ab,kw AND ("spared nerve injury"):ti,ab,kw: (((1 OR 3) AND 3 AND 5) OR ( 5 Austin et al, 2012;Bráz et al, 2012;Wardill et al, 2016;Shen et al, 2017;Ramakrishna et al, 2019;Yang et al, 2019;Brandon-Mong et al, 2020;Chen et al, 2021;Cuozzo et al, 2021;Ding et al, 2021;Lian et al, 2021), a single in vitro study (Castelli et al, 2018), and a single randomised controlled trial (RCT) with 327 enrolled participants, Table 2 (Ellis et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Co-occurrence network analyses based on metagenomic and amplicon sequences have been frequently used to infer microbial relations in environmental or host microbiomes, and further predict microbial interactions (positive or negative) in these environments 9 , 23 , 24 , 40 , 41 , which are informatic for discovering the true microbial interactions attributing to either microbial properties (such as metabolic coupling, nutrient competition, etc.) or from environmental filtration (such as responding similarly to environmental factors or due to physical separation) 42 , 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Microbial co-occurrence networks are composed of nodes [operational taxon units (OTUs)] and edges (predicted relations among microbes) 9 , 23 , 24 . The more nodes and edges, the more complex the microbial co-occurrence networks 25 , 26 .…”
mentioning
confidence: 99%
“…It is well-studied that gut microbes influence many biological processes including immunity, metabolism, and central nervous system (CNS) ( 10 12 ). The effects of gut microbiota on NPP animal models have also been characterized ( 13 , 14 ). Extensive studies have shown that the microbiota can directly or indirectly influence brain homeostasis through affecting anxiety and the occurrence of neurological diseases were related to nerve conduction dysfunction in animal models ( 15 ).…”
Section: Introductionmentioning
confidence: 99%